The effects of acute exercise on episodic memory function among young university students: moderation considerations by biological sex - Lauren Johnson; Paul D. Loprinzi (Tabriz University of Medical Sciences, 2019)
Background: The objective of this study was to evaluate potential sex-specific differences on episodic memory function and determine whether sex moderates the effects of acute exercise on episodic memory.Methods: A randomized controlled intervention was employed. This experiment was conducted among young University students (mean age = 21 years). Both males (n=20) and females (n=20)completed two counterbalanced laboratory visits, with one visit involving a 15-minute bout of moderate-intensity exercise prior to the memory task. The control visit engaged in a time matched seated task. Memory function (including short-term memory, learning, and long-term memory) was assessed from the RAVLT (Rey Auditory Verbal Learning Test).Results: We observed a significant main effect for time (P<0.001, ƞ2p= 0.77) and a marginally significant main effect for sex (P=0.06, ƞ2p= 0.09), but no time by sex by condition interaction(P=0.91, ƞ2p= 0.01). We also observed some suggestive evidence of a more beneficial effect of acute exercise on memory for females. Conclusion: In conclusion, females outperformed males in verbal memory function. Additional research is needed to further evaluate whether sex moderates the effects of acute exercise on memory function.